Monitoring Growth and Development of Toddlers ( 12 – 59 Months) in the Baloi Permai Public Health Center Working Area, Batam City (Jurnal Ilmu Kesehatan Masyarakat, 2020)
Toddlers are the age group that most often suffer from malnutrition and lack of nutrition. Based on data  from the Batam City Health Office in 2017 regarding the scope of monitoring the growth and development of infants at 49.6% of the target set by the Ministry of Health of the Republic of Indonesia which is 80%. Baloi Permai Public Health Center is the lowest public health center with 35.8% achievement coverage. This study aims to analyze of monitoring growth and development of toodlers in the working area of Baloi Permai Public Health Center. The study design used qualitative methods. The number of informants in this study were 8 people. Data analysis using content analysis methods. The results of this study indicate that coordination of growth and development monitoring for toddlers is pooled interdependence, lack of standard operating procedure and standardization of skills. Indirect supervision in the form of recording and reporting has not been implemented. Coordination in monitoring the growth and development of toddlers in the working area of Baloi Permai Public Health Center is not optimal so it needs cooperation with related parties and the active role of all parties to reach the scope of growth and development of toddlers.